The sycamore lace bug Corythucha ciliata Say, 1832 (Hemiptera: Tingidae) — is a potentially dangerous invasive species in the phytocenoses of Kyiv - O. Borzykh; V. Fedorenko; O. Stryhun; P. Chumak; S. Vyhera; O. Honcharenko; T. Galagan; O. Anol; Ie. Kivel; S. Tkachova (Карантин і захист рослин)
Goal. To improve the methodology of effective phytosanitary monitoring of plane trees growing in botanical gardens, parks, garden squares and street plantings of Kyiv.